2012
DOI: 10.1021/bc300015f
|View full text |Cite
|
Sign up to set email alerts
|

Development of Human Hepatocellular Carcinoma Cell-Targeted Protein Cages

Abstract: We described herein a human hepatocellular carcinoma (HCC) cell-targeted protein cage for which the HCC-binding peptide termed SP94 was modified at the surface of a naturally occurred heat shock protein (Hsp) cage. Six types of HCC-targeted Hsp cages were chemically synthesized using two types of heterobifunctional linker (SM(PEG)(n)) with different lengths and two types of SP94 peptide, which contained a unique Cys residue at the N- or C-terminus of the peptide. These Hsp cages were characterized using matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…Similarly, the published result of Toita et al explained that more flexible longer linkers could make the binding of drug carriers to cells easier. 30 Therefore, the feasibility of the DOX-linker-Fbg microsphere-based drug carrier system was confirmed by the cell experiments.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, the published result of Toita et al explained that more flexible longer linkers could make the binding of drug carriers to cells easier. 30 Therefore, the feasibility of the DOX-linker-Fbg microsphere-based drug carrier system was confirmed by the cell experiments.…”
Section: Discussionmentioning
confidence: 90%
“…Studies that they implemented on mice bearing HCC xenografts confirmed the targeting efficiency of SP94 and demonstrated the superior targeting ability of SP94 over the phage clone PC94 and the enhanced therapeutic effect of SP94-LD compared with control peptide conjugated LD (CP-LD) and LD. Toita et al 188 formulated HspG41C-SM(PEG)n-SP94 peptide conjugates by modifying a naturally occurred heat shock protein cage (HspG41C cage) with SP94 through the heterobifunctional linker (SM(PEG)n). The cellular binding investigation demonstrated the binding selectivity of this conjugate to human HCC-derived cell lines, while suggesting that the binding efficiency could be influenced by the amount of SP94 peptides on Hsp cages, conjugation site of SP94 peptide, and linker length between a Hsp cage and a SP94 peptide.…”
mentioning
confidence: 99%
“…Also, for in vivo application, specific drug delivery to target cells was very important in order to avoid any undesirable side effects. An advantage of Hsp cages is that the peptide ligand can be modified by the chemical/genetic method, 22,23 enabling the delivery of cytotoxic reagents to specific cells. It was previously reported that Hsp cages could specifically target human hepatoma cells after binding human hepatoma binding peptides (SP94 peptides) to the surface of the Hsp cages using poly(ethylene glycol) linkers.…”
Section: Future Plansmentioning
confidence: 99%
“…The resulting HspSP94 cage was specifically taken up by human hepatoma cells but not by normal liver cells. 22 Accordingly, an attempt will be made to modify the peptide to Hsp cages and changing the linker between Hsp and DOX to a more acid-responsive linker, which will enhance the usefulness of Hsp cages in a drug delivery system.…”
Section: Future Plansmentioning
confidence: 99%
See 1 more Smart Citation